2016
DOI: 10.1515/manment-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Classical and modern concepts of corporate governance (Stewardship Theory and Agency Theory)

Abstract: Summary The main issues in efficiency of a company as an organisation are relations between the Supervisory Board and the Management Board of a company, and the methods of functioning of Supervisory Boards in governance systems of a company. The classical and modern approach to the role, place, and importance of corporate governance presented in this article, is yet another prompt to continue searching for the optimum in the organisational, economical, and social meaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 3 publications
0
33
0
3
Order By: Relevance
“…The corporate governance structure generally consists of General Meeting of Shareholders, the board of commissioners, the board of directors, and committees under the board of commissioners which include audit committee, risk monitoring committee, and nomination and remuneration committee. Previous studies revealed that the board of directors and audit committee were the most important parties in the corporate governance structure (Xie, Davidson, and DaDalt 2003;Bonazzi and Islam 2007;Andres and Vallelado 2008;Glinkowska and Kaczmarek 2015;Samaha, Khlif, and Hussainey 2015). In addition to the board of directors and audit committee, the structure of sharia governance has a uniqueness that is not owned by conventional companies that also play an important role in the structure of corporate governance, namely the sharia supervisory board (Hamza 2013;Srairi 2015).…”
Section: Sharia Governancementioning
confidence: 99%
See 2 more Smart Citations
“…The corporate governance structure generally consists of General Meeting of Shareholders, the board of commissioners, the board of directors, and committees under the board of commissioners which include audit committee, risk monitoring committee, and nomination and remuneration committee. Previous studies revealed that the board of directors and audit committee were the most important parties in the corporate governance structure (Xie, Davidson, and DaDalt 2003;Bonazzi and Islam 2007;Andres and Vallelado 2008;Glinkowska and Kaczmarek 2015;Samaha, Khlif, and Hussainey 2015). In addition to the board of directors and audit committee, the structure of sharia governance has a uniqueness that is not owned by conventional companies that also play an important role in the structure of corporate governance, namely the sharia supervisory board (Hamza 2013;Srairi 2015).…”
Section: Sharia Governancementioning
confidence: 99%
“…The board of directors plays a role in designing efficient control mechanisms for corporate governance (Bonazzi and Islam 2007;Said, Hj Zainuddin, and Haron 2009). The board of directors elected by shareholders makes the most critical decisions, such as yearly financial settlement, accepts strategies and business plans for the following year, and profit distribution (Glinkowska and Kaczmarek 2015). The board of directors generally has the duties and responsibilities in managing the company, implementing the principles of good corporate governance, preparing business plans, establishing and communicating strategic policies to all stakeholders, and preparing financial reporting.…”
Section: Board Of Directorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This directors' role is one of the key point in good governance practices, which is highlighted on Samuel, Deoga, Jeannada & Immanuel The Role of Forensic Accountants the contemporary agency theory. Agency theory is preferable to view this matter as it can capture the conflicts between the owners, directors, employees, and other employees (Donaldson & Davis, 1991;Glinkowska & Kaczmarek, 2015;Yang & Tan, 2012). Plessis, Hargovan, & Bagaric (2012) argues that directors, as an agent of company, areresponsible to merely serve the owners' interest through well-managed leadership towards the managers' decisions and policy implementation.…”
Section: Motives Behind Fraudulent Liquidationmentioning
confidence: 99%
“…4 They are agency theory and stewardship theory. 5 According to Bosse and Phillips, 6 the agency theory presupposes that owners (principals) and managers (agents) of organizations have diverse interests. However, asymmetric information and prospective opportunistic character of agents make it complicated or expensive for owners or principals to validate the actions of agents.…”
Section: Introductionmentioning
confidence: 99%